Pengaruh Motivasi Berprestasi, Empowerment dan Etos Kerja terhadap Kinerja - Suastina, I Made; Kawiana, I Gede Putu; Suputra, Gusti Alit (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
Background of this research is problems related to employee performance at UPTD. Puskesmas Petang I. Performance is one of the important factors in the survival of a company or agency. The purpose of this study was to examine the effect of achievement motivation, empowerment and work ethic on employee performance. Data collectted with  observation, interviews, documentation, literature and questionnaires. The sample used in this study were 47 respondents. Data analyzed with Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t Test and F Test. The test results showed that (1) achievement motivation has a positive and significant effect on employee performance, (2) empowerment has a positive and significant effect on employee performance, (3) work ethic has a positive and significant effect on employee performance, (4) simultaneously achievement motivation, empowerment and work ethic have a positive and significant effect on employee performance.